2017
DOI: 10.1002/adsc.201701247
|View full text |Cite
|
Sign up to set email alerts
|

Formal [5+3] Cycloaddition of Zwitterionic Allylpalladium Intermediates with Azomethine Imines for Construction of N,O‐Containing Eight‐Membered Heterocycles

Abstract: A formal [5 + 3] cycloaddition of zwitterionic allylpalladium intermediates with 1,3-dipoles is developed, providing N,O-containing eight-membered heterocyclic compounds in high yields. Catalytically generated zwitterionic allylpalladium intermediates in situ from vinylethylene carbonates or vinyloxiranes acted as dipolarophile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(40 citation statements)
references
References 66 publications
(16 reference statements)
0
37
0
2
Order By: Relevance
“…[38] Thep resence of ab identate phosphine ligand was crucial to prevent binding of the NHC to the active palladium catalyst. Thee nantioselective synthesis of seven-membered structures and beyond is quite challenging due to unfavorable entropy effects and transannular interactions.Thus,these annulation reactions reported by Zhao [37] and Glorius [38] pave the way for the asymmetric synthesis of challenging larger-ring macrocycles. [39]…”
Section: Methodsmentioning
confidence: 88%
“…[38] Thep resence of ab identate phosphine ligand was crucial to prevent binding of the NHC to the active palladium catalyst. Thee nantioselective synthesis of seven-membered structures and beyond is quite challenging due to unfavorable entropy effects and transannular interactions.Thus,these annulation reactions reported by Zhao [37] and Glorius [38] pave the way for the asymmetric synthesis of challenging larger-ring macrocycles. [39]…”
Section: Methodsmentioning
confidence: 88%
“…The stepwise [5 + 3] cycloaddition process leading to the formation of the architecturally challenging bridged carbocyclic motif represents the first example of this mode of reactivity in gold catalysis and which has remained conspicuously limited in organic synthesis. [12] Our studies suggest the origin of the observed chemoselectivity was afforded by the extent of the carbocation character in the resonance structure of the proposed in situ formed gold carbenoid species and the realization of charge alteration during the stepwise higher-order cycloaddition pathway. [11] We envision that the present synthetic study will encourage the further development of chemoselective strategies to increase structural diversity in gold catalysis where there is the possibility to fine-tune the stereoelectronic environment of an in situ generated organogold species.…”
Section: Resultsmentioning
confidence: 69%
“…Achieved in good to excellent product yields for a wide variety of substrates, the stepwise higher-order cycloaddition reaction is unprecedented in gold catalysis and examples of which are uncommon in organic chemistry. [12] Added to this, the proposed bridged carbocyclic ring-forming mechanism delineates an example of an increasingly important new facet within the field concerning ligand-controlled chemoselectivity. [11] A density functional theory (DFT) calculation on the origin of the observed product selectivity is also presented.…”
Section: Introductionmentioning
confidence: 99%
“…Handelte es sich bei R 1 um eine Arylgruppe,t rat eine [5+ +4]-Anellierung auf und neungliedrige Benzofuran-fusionierte Heterocyclen wurden selektiv gebildet. Diese Anellierungsreaktionen von Zhao [37] und Glorius [38] ebnen den Wegf ürd ie asymmetrische Synthese herausfordernder hçhergliedriger Makrocyclen. [37a] Zusätzlich zu den oben beschriebenen Anellierungsreaktionen entwickelten Glorius und Mitarbeiter die erste auf VCCs basierende enantioselektive [5+ +2]-Cycloaddition unter Verwendung eines dualen Katalysators.D ieser Katalysator basierte auf einer chiralen NHC-und Pd-Allylspezies,welche vom VCC abgeleitet werden konnte (Schema 10, Wegb).…”
Section: Reaktionen Von Vccs Mit Elektrophilenunclassified
“…Die enantioselektive Synthese von sieben-und hçhergliedrigen Strukturen ist aufgrund ungünstiger Entropieeffekte und transannularer Wechselwirkungen anspruchsvoll. Diese Anellierungsreaktionen von Zhao [37] und Glorius [38] ebnen den Wegf ürd ie asymmetrische Synthese herausfordernder hçhergliedriger Makrocyclen. [39]…”
Section: Reaktionen Von Vccs Mit Elektrophilenunclassified